PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP LEVERAGE PADA PERUSAHAAN PARIWISATA DAN PERHOTELAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Noval Alief Rahman Aditya (CV. ADIBA AISHA AMIRA, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure on leverage in tourism and hospitality companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. CSR disclosure was measured using the Global Reporting Initiative (GRI) Standards index comprising 48 disclosure items, while leverage was measured using the Debt-to-Asset Ratio (DAR). The population consists of 26 companies in the tourism, hotel, and restaurant sub-sector, yielding 94 firm-year observations after eliminating extreme outliers. Ordinary Least Squares (OLS) regression was employed as the analytical method, processed using IBM SPSS Statistics 26. The results indicate that CSR disclosure does not have a statistically significant effect on leverage (β = 0.103, t = 0.804, p = 0.424 > 0.05), with a coefficient of determination (R²) of only 0.007. These findings suggest that the level of CSR disclosure by tourism and hospitality firms in Indonesia has not been a determining factor for their capital structure decisions in the study period, possibly due to industry-wide recovery dynamics following the COVID-19 pandemic.